Design and Kinematics Analysis of the Three-configuration Old Helper Metamorphic Mechanism based on Graph Theory - Sunke Zhu; Lü Hang; Weizhan Li; Yanli Yin; Yao Zhao (Jixie chuandong)
In order to develop an old helper robot， based on the graph configuration theory and the numerical synthesis， a three-configuration old helper mechanism that can switch between 2 degrees of freedom， 1 degree of freedom， and 0 degrees of freedom is designed. Aiming at the 2-DOF walking configuration of the metamorphic mechanism， the closed-loop vector method is used to analyze the kinematics， and the displacement， velocity and acceleration of the key position of the metamorphic mechanism in this configuration are obtained. The analysis results show that， the displacement curve changes greatly when the support period transitions to the swing period， and the speed and acceleration change greatly within the last 40% of the gait cycle， which is in line with the law of human gait， indicating that the old helper mechanism design is reasonable.